Larval application of sodium channel homologous dsRNA restores pyrethroid insecticide susceptibility in a resistant adult mosquito population. Issue 1 (December 2016) - Bona, Ana; Chitolina, Rodrigo; Fermino, Marise; de Castro Poncio, Lisiane; Weiss, Avital; Lima, José; Paldi, Nitzan; Bernardes, Emerson; Henen, Jonathan; Maori, Eyal
Abstract Background Mosquitoes host and pass on to humans a variety of disease-causing pathogens such as infectious viruses and other parasitic microorganisms. The emergence and spread of insecticide resistance is threatening the effectiveness of current control measures for common mosquito vector borne diseases, such as malaria, dengue and Zika. Therefore, the emerging resistance to the widely used pyrethroid insecticides is an alarming problem for public health. Herein we demonstrated the use of RNA interference (RNAi) to increase susceptibility of adult mosquitoes to a widely used pyrethroid insecticide. Methods Experiments were performed on a field-collected pyrethroid resistant strain ofAe. aegypti (Rio de Janeiro; RJ). Larvae from the resistantAe. aegypti population were soaked with double-stranded RNAs (dsRNAs) that correspond either to voltage-gate sodium channel (VGSC), P-glycoprotein, or P450 detoxification genes and reared to adulthood. Adult mortality rates in the presence of various Deltamethrin pyrethroid concentrations were used to assess mosquito insecticide susceptibility. Results We characterized the RJAe. aegypti strain with regard to its level of resistance to a pyrethroid insecticide and found that it was approximately 6 times more resistant to Deltamethrin compared to the laboratory Rockefeller strain. The RJ strain displayed a higher frequency of Val1016Ile and Phe1534Cys substitutions of the VGSC gene. The resistant strain also displayed a higher basal expression level of VGSC compared to the Rockefeller strain. When dsRNA-treated mosquitoes were subjected to a standard pyrethroid contact bioassay, only dsRNA targeting VGSC increased the adult mortality of the pyrethroid resistant strain. The dsRNA treatment proved effective in increasing adult mosquito susceptibility over a range of pyrethroid concentrations and these results were associated with dsRNA-specific small interfering RNAs in treated adults, and the corresponding specific down regulation of VGSC gene expression level. Finally, we demonstrated that the efficiency of our approach was further improved by 'tiling' along the VGSC gene in order to identify the most potent dsRNA sequences. Conclusions These results demonstrate that dsRNA applied to mosquito larvae retains its biological activity into adulthood. Thus, the RNAi system reported here could be a useful approach to control the widespread insecticide resistance in mosquitoes and other insect vectors of human diseases.